Microwave-assisted green synthesis of silver nanoparticles by extracts of fig fruits and myrrh oleogum resin and their role in antibacterial activity - Jamilah A. Alsulami; Kahkashan Perveen; Muneera R. Alothman; Latifah A. Al-Humaid; Faris M. Munshi; Rabi'atul Adawiyah Ahmad; R.Z. Sayyed; Shifa Khan (Journal of King Saud University: Science, 2023)
Multidrug-resistant bacteria hindering disease management have become a matter of serious concern. Nanotechnology has evolved as a fresh promise for managing infectious diseases. The intended purpose of this study was to synthesize silver nanoparticles using fig fruit (Ficus carica) and myrrh oleogum resin (Commiphora sp.) extracts and microwave irradiation. UV–visible, FTIR, TEM, DLS and Zeta-potential analysis were deployed to characterise silver nanoparticles. The synthesized nanoparticles were assessed for antibacterial activity against four pathogenic bacteria, and their effects on the bacteria's cells were examined as well through SEM. Fig fruit and myrrh’s extract reaction solution changed color (reddish brown) after 90 and 120 s of microwave operation, respectively. UV–Vis-validated the synthesis of silver nanoparticles with fig fruit extract (FAgNPs) and myrrh extract (MAgNPs), showing absorption bands between 434.41 nm and 434.95 nm. TEM revealed that the FAgNPs and MAgNPs were predominantly spherical and of various sizes. The average diameter of FAgNPs and MAgNPs was 33.79 nm and 31.63 nm, respectively, and both of them were moderately polydispersed and relatively stable colloids. The antibacterial evaluation of FAgNPs shows that the highest level of inhibition was against S. aureus and it was higher than that of Augmentin, and next to it were E. coli and S. pyogenes. While in case of MAgNPs the most sensitive pathogen was S. aureus, followed by E. coli and S. pyogenes, respectively. FAgNPs and MAgNPs had MIC values of 15 µg/ml against S. aureus, compared to 30 µg/ml against E. coli. SEM images showed that treatment with FAgNPs and MAgNPs caused S. aureus cells to become malformed. Similar cell damage was also observed in E. coli cells treated with FAgNPs and MAgNPs. This study for the first time report the synthesis of silver nanoparticles utilizing fig fruit and myrrh extracts and microwave irradiation.